Peran Dan Aktualisasi Nilai-Nilai Pancasila Sebagai Ideologi Negara Di Era Masa Kini - Aprilla, Nina (Philosophiamundi, 2025)
Pancasila, as the state ideology of Indonesia, holds a pivotal role in shaping the nation’s socio-political direction, particularly amid rapid shifts driven by globalization, technological advancements, and the evolving democratic landscape. These developments have challenged the relevance of Pancasila’s values, reflected in societal disorientation, rising polarization, and diminishing ethical exemplars in public life. This paper departs from the need to reaffirm Pancasila’s function as both a normative foundation and an ethical compass capable of maintaining social cohesion and preventing fragmentation. The purpose of this study is to examine how Pancasila’s core values are being actualized in contemporary national life and to assess the extent to which the ideology can strengthen socio-political stability in the modern era. By analyzing current socio-political dynamics, this article underscores the urgency of revitalizing Pancasila as a guiding framework for thought, conduct, and civic responsibility within an increasingly complex society.